Employee’s personal hardcopy archival and employee management Of Robi Axiata Limited. - Khan, Nuzhat Tabassum (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.